ECONOMIC VALUATION OF THE MOLUCCAN ECLECTUS BASED ON MARKET PRICE AND MAINTENANCE COST APPROACH - Ilham Setiawan Noer; Yanto Santosa; Dede Aulia Rahman (Department of Forest Resources Conservation and Ecotourism - IPB University, 2022)
Illegal wildlife trade is a criminal act of enormous value, almost equivalent to drug trafficking. One species vulnerable to being traded illegally is the moluccan eclectus which has a high number of enthusiasts. Law enforcement in cases of illegal wildlife trade in Indonesia is difficult because there is no standardization in calculating the economic value of wild animals. The economic valuation approach is one approach in quantifying the economic value of wildlife. This study aims to analyze the economic value of moluccan eclectus based on the market price approach, analyze the economic value of moluccan eclectus based on the maintenance cost approach, and compare the two approaches in the economic valuation of moluccan eclectus. Data were collected by two methods, namely literature study and interviews. The literature study collects data in the form of moluccan eclectus market prices circulating in the domestic and international markets. Meanwhile, interviews were conducted with managers of conservation institutions at Siantar Zoo, Medan Zoo, Tasikoki Animal Rescue Center (PPS) Manado, Taman Mini Indonesia Indah Bird Park in Jakarta, Kekewang Zoo in North Sulawesi, and Andy Hoo Captivity in East Java to obtain data on maintenance cost. Data analysis was carried out quantitatively and qualitatively. The results showed that the economic value of moluccan eclectus based on the market price approach reached IDR 16,138,820/individual. Meanwhile, based on the maintenance cost approach, the economic value of moluccan eclectus reaches IDR 6,313,333/individual. Based on the accuracy of the results, both approaches have the same level of accuracy. Meanwhile, based on the effectiveness and cost-efficient aspects of data collection and analysis, the market price approach is relatively better than the maintenance cost approach. Key words: Economic valuation, illegal wildlife trade, moluccan eclectus